Perceived Academic Workload and Its Impact on Burnout among Architecture Students - Abdulwahhab, Mayyadah Lutfi; Jbur., Abeer Qasim; Hussein, Abdulbaqi Ghazi (Language, Literature and Education: Research Updates Vol. 5, 2025)
Student burnout can be defined as a state of emotional exhaustion that students experience in the learning process, due to psychological pressure, academic workload, or other psychological factors, as well as a tendency towards personality breakdown and a feeling of decreased personal achievement. In architecture education, students may face different challenges related to workloads, practical training, and concerns about stress-induced fatigue. The research aims to study the relationship between academic workload and its role in student stress, fatigue, and burnout. A survey was conducted with 63 fourth-year students in the Department of Architecture at the College of Engineering at Al-Mustansiriya University. An academic workload scale was constructed based on previous studies, along with a modified burnout scale according to the nature of the architecture department. The research presents a discussion of the academic workload as an important factor that affects students and how they perceive the nature of the curriculum and cope with the psychological pressures generated from it in architectural education. It also defines burnout in architectural education. The data was statistically analysed using partial least squares structural equation modelling with the Smart-PLS4 program and statistical analysis using SPSS v.28 for the study variables. The research confirms the complex nature of the concept of academic workload and highlights the need to distinguish between perceived quantitative (Actual time investment and curriculum design) and qualitative (teaching style, learning environment and personal traits) workload and their impact on students' burnout. The results identified the dimensions of academic workload that affected the levels of fatigue among architecture students. It showed that all dimensions of academic workload influence burnout, with teaching methods and learning environment having the most impact on burnout, followed by course management, and personal characteristics ranking last. The study recommends that the Department of Architecture periodically review students' academic workload, psychological well-being and introduce effective curriculum design to minimise burnout and enhance their learning outcomes.